2016
DOI: 10.12659/msm.895755
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Detection, Discrimination, and Risk of Breast Cancer According to Anisotropy Parameters of Diffusion Tensor Imaging

Abstract: BackgroundThe aim of this study was to investigate whether the anisotropy parameters are helpful in the detection and discrimination of breast cancers, and to determine its value in predicting the risk of cancers.Material/MethodsThere were 56 patients with 56 lesions (34 malignant, 22 benign) included in the study. DTI was performed in every patient and apparent diffusion coefficient (ADC), fractional anisotropy (FA), and eigenvalues E1, E2, and E3 were measured in every lesion and the normal breast tissue.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Three studies for MD (9, 12, 18) and four studies for FA values (9, 12, 18, 24) used in the differentiation between two subtypes of breast cancer were further pooled. The SMD of MD was −0.76 (−1.40, −0.12), P = 0.02, which indicated that IBC had a lower MD value than that of DCIS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies for MD (9, 12, 18) and four studies for FA values (9, 12, 18, 24) used in the differentiation between two subtypes of breast cancer were further pooled. The SMD of MD was −0.76 (−1.40, −0.12), P = 0.02, which indicated that IBC had a lower MD value than that of DCIS.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that a larger area of liquefactive necrosis more easily occurs in a highly aggressive and large tumor, which may result in a loss of organization of the breast parenchyma in cancerous tissues, and in reverse reduce the anisotropy to a certain extent in breast cancer, as well as the difference of FA between breast cancer and benign lesions. It may be the reason that FA reported in some of the included studies cannot distinguish breast cancer from benign lesions (9, 18, 19). FA also performed a moderate diagnostic value, with the lowest AUC of 0.76 among the three parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas it is suggested that reduced structuring in malignant breast lesions should be reflected by a reduced diffusion anisotropy (66), anisotropy measures achieved a mixed diagnostic utility; some studies find no significant difference in fractional anisotropy between malignant and benign lesions (40,57). The number of diffusion directions used ranged from six to 64, though use of the b value pair 0 and 1000 sec/mm 2 was the most common (27,40,57,66).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Kurtosis can also be combined with IVIM. 30 Diffusion tensor (DT) modelling has produced inconsistent results, generally demonstrating lower fractional anisotropy (FA) in cancers compared with normal tissues, 31,32 but not always showing a distinction from benign lesions; 15,33,34 other anisotropy metrics may be more sensitive. 35 Furthermore, the source of anisotropy is uncertain: a preclinical breast cancer model observed lower FA in hypoxic regions with lower collagen fibre content, 36 but the differences between normoxic and hypoxic FAs were small, approximately 0.03.…”
Section: Introductionmentioning
confidence: 99%